Economic Impacts of Natural Disasters in Megacities: The Case of Floods in S\~ao Paulo, Brazil - Eduardo Haddad; Eliane Teixeira (European Regional Science Association (ERSA), 2013)
The city of S\~ao Paulo, home to 11 million people, suffers constantly the effects of flooding caused by extreme precipitation. Localized floods occur every summer in various parts of the city. Besides the losses and inconvenience felt by the residents, floods produce damages that cross the city boundaries, affecting income and output in the metropolitan area as well as in other parts of the state and the country. The objective of this study is to evaluate the economic impacts of floods in the city of S\~ao Paulo through the use of a spatial CGE model integrated to GIS information related to the location of points of floods and the firms within their influence. It is estimated that floods contributed to reduce city growth and residents welfare, as well as to hamper local competitiveness in both domestic and international markets. An intra-city total impact-damage ratio of 2.2 and an economy-wide total impact-damage ratio of 5.0 were found.
Keywords: 330; climate change; natural disasters; flooding in S\~ao Paulo; spatial CGE; GIS